‘The Color of the Grave is Green’ – Moss and Juniper in Early Medieval Graves at Toppolanmäki, Finland - Moilanen Ulla; Juhola Tytti; Pätsi Sanna; Vanhanen Santeri; Alenius Teija (Routledge, 2022)
Two graves, initially discovered in the 1930s, were reopened and examined in 2017 and 2018 at the Early Medieval cemetery of Toppolanmäki, Finland. Soil samples taken from the graves were sampled for macrofossils, pollen and microfauna. Pollen and spore analysis provided possible evidence for the use of mosses and juniper branches in the graves. Also, moss-indicating microfauna (Euglypha spp.) was detected. At Toppolanmäki, mosses were used in both coffins and earth burials. The clubmoss found in the latter could even indicate the presence of a woven carpet or mattress in the grave pit. The use of juniper, on the other hand, could indicate ritual continuation from the Iron Age as it is a common find in older cemeteries. It is also possible that the early medieval environment around the site was characterised by dry meadows and juniper bushes at the time of the burial, and even that one of the burials took place in early summer. The study highlights the research potential of graves that have been excavated decades ago and presents a new biological indicator of the use of moss in burials: the testate amoeba Euglypha.